Spatial Audio Cueing Aids Pilot Navigation during Simulated Helicopter Flight in Degraded Visual Environments. (November 2019) - Milam, Lana; Akins, Ellis; Williams, Henry; Simpson, Brian; Jones, Heath G.
Aviation mishaps resulting from degraded visual environments (DVEs) represent a significant loss in military personnel and aircraft every year. DVEs can be caused by any type of environmental condition (e.g., sand, snow, fog) that obstructs the pilot's vision, and can cause spatial disorientation. The current study was a tri-service effort exploring the implementation of spatial audio cueing to aid pilot navigation in DVEs. Directional cueing (i.e., indicating the location of target waypoints) was achieved by spatializing an auditory stimulus. Pilots performed multiple flight maneuvers in a full-motion UH-60 Black Hawk flight simulator at the U.S. Army Aeromedical Research Laboratory. Performance was assessed by measures of error, completion time, and failure rate. Findings from this study provide information on sensory cueing display design for helicopter flight in DVEs.